The Extraction of Metals from Industrial Hazardous Wastes and the Production of a Non-Hazardous Residue - LuisW. Pommier (The Minerals, Metals and Materials Society, 1998)
The industrial wastes generated by the plating industry, the circuit board manufacturing industries and other related industries normally contain high concentrations of metals, which make them hazardous. The extraction of the contained metals and their separation may be achieved by both pyro and hydro metallurgical processes. Some of the industrial wastes, those rich in some metals like nickel for instance, are being treated like mine ore concentrates and are being fed to smelting furnaces. The slags from these smelter operations are hazardous. They have, however, special environmental dispensations issued by the regulatory authorities. Hydro-metallurflcal processes have been reported. They also generate a residue which is hazardous because not all the valuable metals are leached out and also, because "non valuable" components, like chromium, are less readily leached. Residues from the plating industry, containing nickel, copper. zinc, iron and chromium as the major constituents and also sodium and calcium, together with cadmium, cobalt, lead. manganese, magnesium, molybdenum, and potassium, have been processed for the extraction of the valuable components. The generation of electrolytic nickel, copper and zinc and also of ferric chloride and chromium oxide is reported. The operation is achieved by a caustic leach for the extraction of zinc, followed by a sulfuric acid leach for the extraction of nickel and copper. This acid leach also extracts the iron and some chromium. The nickel copper and zinc are rendered pure by electrolysis, the iron is oxidized for the production of ferric chloride and the chromium is recovered as an oxide. The leaching operation is performed in two stages, first at a pH of 2.5 to generate an electrolyte for the partial recovery of the metals and then at a pH of 0.5 for the complete extraction of the metals. This leaching operation generates a residue, which although small in volume compared to the initial feed, still contains traces of the valuable metals and a portion of the chromium which makes it hazardous. Additional leaching with hydrochloric acid or nitric acid is required for its complete dissolution. The other minor constituents mentioned are present in concentrations each of less than 0.1% and are handled as impurities in the process. The metals which are soluble at a pH 0.5 and precipitate between 0.5 and 2.0 are bled off. Other impurities will concentrate on the raffinate from the solvent extraction operations from whence they are bled off. These bleeding streams are hazardous and the "impurity metals" are now present in concentrations which would make them valuable, however, the size of these streams is so small that they do not warrant their processing, however they could be marketed to specialized smelters. The extraction of the valuable metals, of the hazardous constituents, the generation of a marketable mixture of minor constituents and the production of a non-hazardous residue for declassification is profitably achieved.